2018
DOI: 10.1186/s13638-018-1217-z
|View full text |Cite
|
Sign up to set email alerts
|

An anonymous batch handover authentication protocol for big flow wireless mesh networks

Abstract: Wireless mesh network (WMN), as a new generation of wireless network technology, has raised increasing concerns in recent years. Due to the strong mobility nature of the clients in WMNs, the handover events frequently occur. Therefore, taking into consideration the openness of the wireless communication channel, the handover authentication protocols for WMNs have to be both efficient and secure, which remains a challenge. In this paper, an anonymous batch handover authentication protocol is proposed using grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Fourth, AS verifies the ticket and the client in a multi-hop fashion that leads to authentication delay. Wang et al [19] proposed a batch handover authentication protocol based on the pre-distribution of handover keys to minimizing the authentication delay. The protocol preserved the privacy of the client where the identity of the foreign mesh router (MRj) and timestamp of the client (TMCi) was unknown to the attacker; however, storing these pre-distributed tickets consumed massive storage space at the client side, which are resource-constrained.…”
Section: Related Workmentioning
confidence: 99%
“…Fourth, AS verifies the ticket and the client in a multi-hop fashion that leads to authentication delay. Wang et al [19] proposed a batch handover authentication protocol based on the pre-distribution of handover keys to minimizing the authentication delay. The protocol preserved the privacy of the client where the identity of the foreign mesh router (MRj) and timestamp of the client (TMCi) was unknown to the attacker; however, storing these pre-distributed tickets consumed massive storage space at the client side, which are resource-constrained.…”
Section: Related Workmentioning
confidence: 99%
“…Yang.X et al [18] [23] uses group signature scheme. But since it uses elliptic curve cryptography (ECC) for group signature, it involves huge computational overhead.…”
Section: Related Workmentioning
confidence: 99%
“…But since it uses elliptic curve cryptography (ECC) for group signature, it involves huge computational overhead. Dongcheng et al 2018 [23] uses group signature scheme. But since it uses elliptic curve cryptography (ECC) for group signature, it involves huge computational overhead.…”
Section: Related Workmentioning
confidence: 99%
“…The results of this experiment showed that the network node was trustworthy and that data transmission was precise. Wang et al [27] suggested an anonymous batch handover authentication protocol that pre-distributes handover keys using a group signature technique. Unlike current group signature protocols, the proposed protocol avoids group signature correlation operations during the handover authentication process, resulting in improved performance.…”
Section: Literature Surveymentioning
confidence: 99%